Mortality Analysis of Covid-19 in The Province of West Sumatera - Nindi Elfiza; Defriman Djafri; Ade Suzana Eka Putri (Faculty of Public Health, Andalas University, 2022)
The rapid and uncontrolled transmission of COVID-19, causes the high morbidity and mortality rates of COVID-19 throughout the world, including West Sumatra (CFR 2.27%). This study aims to analyze the mortality of COVID-19 in West Sumatra and the risk factors that influence it. The research design retrospective cohort using secondary data on COVID-19 cases in West Sumatra from March 26, 2020 to June 7, 2021. The sampling technique is total sampling provided that the sample criteria are met. Data analysis used logistic regression method. 44,693 confirmed cases of COVID-19, 968 (2.17%) died and 43,725 (97.83%) did not die. Factors associated with COVID-19 mortality were age (RR 9.79; 95% CI 8.65-11.09), gender (RR 1.51; 95% CI 1.33-1.71), diabetes (RR 10.21; 95% CI 8.91-11.69), hypertension (RR 6.49; 95% CI 5.59-7.54), cardiovascular diseases (RR 9.57; 95% CI 8.17-11.21), COPD (RR 10.51; 95% CI 7.57-14.57), asthma (RR 2.03; 95% CI 1.23-3.34), and kidney diseases (RR 19.87; 95% CI 16.54-23.86). Kidney diseases are the most dominant factor associated with COVID-19 mortality (RR 16.07; 95% CI 11.34-22.78). COVID-19 patients with kidney disease have the highest risk of death. Treatment of patients with comorbidities must be prioritized and improve health promotion in at-risk groups.